Coordinated and rapid whole‐plant systemic stomatal responses. Issue 1 (3rd October 2019) - Devireddy, Amith R.; Arbogast, Jimmie; Mittler, Ron
Abstract : See also the Commentary on this article by McLachlan, 225 : 5–6 .